أثر التكوين البصري للفراغات المعمارية في استكشاف مسارات الحركة الداخلية في الكليات الطبية حالة دراسية كليات طب الأسنان - ودح هاني هاشم; جندي ميسون خالد (Latakia University Journal -Engineering Sciences Series, 2016)
تزايد الاهتمام في العقود الأخيرة بالجوانب السلوكية في التصميم، كما أشارت الأبحاث إلى وجود صعوبات لدى الأشخاص ليجدوا طريقهم في المباني الكبيرة والمركبة، حتى بعد قضائهم بعض الوقت بها، حيث يعدّ استكشاف المسار Wayfinding تجربة إنسانية يتفاعل فيها المستخدم مع الفراغ المحيط، لحل مشكلة الوصول إلى وجهته، تأتي أهميتها مع تطور الأهداف التعليمية للكليات الطبية نحو تحقيق التكامل بين البرامج التعليمية، والبرامج التصميمية، وبخاصة كلية طب الأسنان التي تتميز بتنوع فئات المستخدمين وتنوع مساراتهم إلى وجهات مختلفة. ينطلق البحث من فرضية مفادها أن استكشاف المسار يكتسب بعداً يتعدى مستوى تحقيق العلاقات الوظيفية للفراغات الانتفاعية، وتوفير فراغات توزيع ومسارات حركة منظمة وسلسة، إلى دراسة الجوانب السلوكية للمستخدمين، والمتعلقة بالانطباعات المباشرة وغير المباشرة للعناصر المعمارية في البيئة المبنية لكليات طب الأسنان. يطرح البحث في القسم النظري تعريفاً بهذا المفهوم، ‏والجوانب السلوكية المرتبطة به، وفي القسم العملي الاعتبارات التصميمية لكليات طب الأسنان الداعمة لهذه العملية، ومن خلال دراسة تحليلية موضوعية لأمثلة محلية وعالمية لكليات طب الأسنان، ليتم الوصول إلى هدف البحث المتمثل بالنقطتين التاليتين: دور التكوين البصري في تحقيق الإدراك الكامل للبيئة المبنية. أهمية الخصائص الفراغية في تحقيق الاستكشاف الأمثل لمسارات الحركة. In recent decades, the interest in the behavioral aspects of the design is increased.The research also pointed to the existence of difficulties with people to find their way in the big and complex buildings , even after spending some time there, where the “Wayfinding”is considered a human experience through which a user interacts with the ambient space, to solve the problem of access to his destination.The importance of this comes with the development of educational goals of the Medical Colleges towards the integration of the educationalprograms , and design programs, particularly the Faculty of Dentistry, which is characterized by the diversity of categories of users and the variety of paths to different destinations. The research starts from the premise that the “Wayfinding” acquires a dimension which is beyond the level of achievement of the functional relationships of the Utilization spaces, providing spaces distribution and organization of cursive and organized movement paths. Besides, it studies the behavioral aspects of users, which are related to the impressions of direct and indirect architectural elements in the built environment of the dental colleges. The research discusses in the theoretical section the concept of “Wayfinding”, and the Behavioral Aspects that associated with itwere identified in the practical; the Design Section considerations that associated with the concept of “Wayfinding”, in the College of Dentistry, were identified by analytical objective study of the local and global examples of dental colleges, to reach the research goal in the following two points: The importance of the visual configuration in achieving thewhole perception of the built environment. The importance of the Spatial Characteristics in achieving the Optimal Wayfinding.